Seasonal Variation of Solar Wind–Geomagnetic Coupling: A Correlation Heatmap Approach (SS Multidisciplinary Research Journal, 2025)
Solar wind–magnetosphere interaction during geomagnetic storm periods is visually demonstrated by the graphics that show the statistical and temporal links between important solar wind parameters and geomagnetic indices. Significant variations in variables including the interplanetary magnetic field (BZ), solar wind proton density, plasma speed, flow pressure, and geomagnetic indices (Dst and AE) are seen in the continuous time series charts. The dynamic solar wind conditions that cause magnetospheric disruptions are reflected in these fluctuations.The degree and direction of inter-parameter dependencies are further demonstrated by the correlation heatmaps for January and July, which show significant negative correlations between BZ and AE or Dst indices and strong positive correlations between proton density and flow pressure. These correlations confirm that southbound BZ components increase geomagnetic activity by encouraging energy transfer and magnetic reconnection into Earth's magnetosphere. In line with other findings in space weather research, the statistics generally support the notion that storm generation and geomagnetic variations are dominated by the interplanetary magnetic field BZ.